Role of oxygen vacancies and Mn sites in hierarchical Mn2O3/LaMnO3-δ perovskite composites for aqueous organic pollutants decontamination - Wang, Y.; Chen, L.; Cao, H.; Chi, Z.; Chen, C.; Duan, Xiaoguang; Xie, Y.; Qi, F.; Song, W.; Liu, J.; Wang, Shaobin (Elsevier BV, 2019)
La-based perovskites are catalytically active owing to the oxygen vacancies, redox metal centers of B sites and surface hydroxyl groups. Nevertheless, the insights into these active centers on environmental catalysis are still insufficient. In this study, hierarchical mixed oxides perovskite microspheres were synthesized for catalytic ozonation over oxalic acid and benzotriazole. LaMn4Ox, with LaMnO3-d as the dominant crystal phase, demonstrated superior catalytic activity to Mn2O3 and LaMnO3 synthesized from citric acid sol-gel method. Temperature-programmed desorption of NH3 (NH3-TPD) and pyridine-Fourier transform infrared spectroscopy (pyridine-FTIR) tests proved Lewis acid as the main acid type. Temperature-programmed reduction of H2 (H2-TPR), O2-TPD and X-ray photoelectron spectroscopy (XPS) analysis indicated the presence of oxygen vacancies and mixed valences of Mn in the crystal structure facilitated the catalytic process. Moreover, the content of oxygen vacancy was calculated by iodometric titration method. With the aid of theoretical calculations, oxygen vacancies were found to exhibit a strong affinity toward ozone adsorption, where ozone molecules spontaneously dissociated into reactive oxygen species (ROS) such as O2[rad]- and 1O2. The B site of Mn facilitated ozone decomposition by extending the O–O bond of ozone due to the electron transfer from Mn3+/Mn4+ redox cycle. In-situ EPR and quenching tests confirmed the contribution of O2[rad]- and 1O2 in benzotriazole degradation along with [rad]OH. This study stepped further to unveil the ozone adsorption/decomposition and ROS generation on nanoscale perovskite-based composites.